Schooling for Sustainable Development in Chinese Communities
300 p.
Keywords: This book focuses on the academic foundations, trends and traditions of environmental education for sustainable development principally in Chinese contexts. It highlights contexts and case studies that illuminate recent Chinese initiatives. It includes case studies of green schools and reports on recent initiatives in school-based ESD curriculum development programmes in China, Hong Kong, Macao and Taiwan. The book concludes with an overview chapter that points to likely future developments. The assumption underpinning the book is that experiences gained in such a major country as China will be of real interest to geographical and environmental educationists, professional educators and teachers elsewhere. Not only will it generate interest and create greater awareness but also it is hoped that these experiences will provide a platform for scholarly exchange and contribute insights on education policy and curriculum changes across Asian-Pacific communities in an increasingly globalised world.